Analysis of equilibrium CO2 solubility and thermodynamic models for aqueous 1‐(2‐hydoxyethyl)‐piperidine solution. Issue 6 (9th April 2019) - Xiao, Min; Zheng, Wenchao; Liu, Helei; Tontiwachwuthikul, Paitoon; Liang, Zhiwu
Abstract: 1‐(2‐Hydoxyethyl)‐piperidine (1‐(2HE)‐PP) is a new tertiary amine with desirable properties and can be potentially used to formulate superior absorbents for CO2 capture. The equilibrium CO2 solubility of 1‐(2HE)‐PP solution is measured over temperatures from 298 to 333 K, CO2 partial pressures from 8.1 to 101.3 kPa and initial amine concentrations from 1 to 5 M. Two thermodynamic models, namely semiempirical model and activity coefficient model are developed for the system. The activity coefficient model shows better estimation solubility with an absolute average relative deviation (AARD) of 7.6%. In the comparison between the two models, a comprehensive analysis is presented. Some suggestions are provided for the similar model development. In addition, the speciation plot of CO2 loaded 1‐(2HE)‐PP solution is predicted based on the activity coefficient model. The predictive pH values agree well with experimental data with AARD of 1.0%. Finally, the potential of 1‐(2‐HE)PP to be an alternative amine in CO2 capture is evaluated.